On "Other War": Lessons from Five Decades of RAND Counterinsurgency Research - Long, Austin (RAND Corporation, 2006)
The challenges posed by insurgency and instability have proved difficult to surmount. This difficulty may embolden future opponents to embrace insurgency in combating the United States. Both the current and future conduct of the war on terror demand that the United States improve its ability to conduct counterinsurgency (COIN) operations. This study makes recommendations for improving COIN based on RANDÂ•s decades-long study of it.